Uncombable hair in a case of Zellweger syndrome - A new association - Yatham Jahnavi; R G Sharada; Afthab Jameela Wahab (Wolters Kluwer Medknow Publications, 2023)
Zellweger syndrome (ZS) is a rare autosomal recessive, peroxisomal biogenesis disorder (PBD) that occurs due to a mutation in any of the thirteen peroxin (PEX) genes. It is reported to manifest with varying degrees of severity, ranging from non-specific gastrointestinal abnormalities, nail and enamel defects to multisystem involvement (cerebro-hepato-renal syndrome, eye, ear, and neurological abnormalities). Uncombable hair syndrome (UHS) is a rare hair shaft disorder characterized by dry, frizzy, unmanageable hair. Diagnosis of UHS can be confirmed by scanning electron microscopy (SEM), which reveals a triangular cross-section of the hair. We report a case of UHS with a hitherto unreported association of ZS (due to a homozygous mutation of PEX 12).